Pengembangan Lab Virtual sebagai Media Interaktif dalam Mengatasi Miskonsepsi Fisika pada Materi Efek Doppler - Thalib, Nurinda; Mursalin, Mursalin; Irsan , Irsan (Lensa: Jurnal Kependidikan Fisika, 2025)
This study aimed to develop a virtual laboratory as an interactive learning medium to address students’ misconceptions in physics, particularly on the Doppler Effect topic. Conducted at SMA Negeri 1 Telaga during the 2024/2025 academic year, the research employed a Research and Development (R&D) approach using a 4D model (Define, Design, Develop, Disseminate), which was implemented up to the Develop stage. The developed media was created using Lectora Inspire 18 and included simulations, theoretical content, and interactive components. Validation involved media experts, content experts, and instructional tool assessment, resulting in high validity scores (average 3.75 for media and 3.50 for content). Practicality was evaluated through classroom implementation and student feedback, both yielding very positive results, with 100% implementation and strong student approval across five evaluation aspects. Effectiveness was measured through student activity observation, misconception analysis, and N-Gain testing, which revealed medium to high improvement in conceptual understanding. The findings demonstrate that the virtual laboratory is valid, practical, and effective in enhancing learning and reducing misconceptions. This study supports the integration of virtual laboratories in physics education to improve conceptual mastery and student engagement in abstract scientific topics.